Investment, uncertainty and irreversibility: evidence from belgian accounting data - Danny Cassimon; Peter-Jan Engelen; Hilde Meersman; Martine Van Wouwe (National Bank of Belgium, 2002)
This paper investigates the effects of uncertainty on the investment behaviour using firm-level data for a sample of Belgian manufacturing firms. In general, the results confirm former analysis at the aggregate level, stating that uncertainty does matter but that the sign of the effect and its magnitude largely depend on which proxies are used and how they are defined. It is shown that uncertainty has mainly an impact on the decision to invest and to a much lesser extent on the amount invested. Furthermore, the difference between reversible and irreversible investment is crucial. The impact of volatility on irreversible investment is far more larger than on reversible investment. In some cases, the amount of reversible investment will increase with higher volatility.
Keywords: D81; D92; C23; 330; investment; uncertainty; irreversibility; Investitionsentscheidung; Investition; Investitionsrisiko; Belgien